2002
DOI: 10.1016/s0140-3664(02)00058-0
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of resource reservation and call admission policies for deterministic services in PGPS-based packet networks

Abstract: Abstract.We address the issue of reserving resources at packet switches along the path of calls requiring a deterministic bound on end-to-end delay. The switches are assumed to schedule outgoing packets using the Packet-by-Packet Generalized Processor Sharing (PGPS) scheduling discipline. We propose an algorithm for call admission control (CAC) and a number of resource reservation policies that are used to map the end-to-end delay requirement into a local rate to be reserved at each switch. The proposed reserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The paper shows that the problem can be solved optimally for several classes of schedulers (including WFQ), and it may or may not have a convex formulation depending on the scheduler class; the results show instead that unequal rate allocation is necessary, since equal rate allocation may fail at very low network loads. Paper [35] proposes several criteria for resource allocation in WFQ-based networks (equal, capacity-proportional, and remaining capacity proportional) and shows how they perform in conjunction with least-loaded-path-first routing. The result is that ERA reduces the call blocking probability.…”
Section: Related Workmentioning
confidence: 99%
“…The paper shows that the problem can be solved optimally for several classes of schedulers (including WFQ), and it may or may not have a convex formulation depending on the scheduler class; the results show instead that unequal rate allocation is necessary, since equal rate allocation may fail at very low network loads. Paper [35] proposes several criteria for resource allocation in WFQ-based networks (equal, capacity-proportional, and remaining capacity proportional) and shows how they perform in conjunction with least-loaded-path-first routing. The result is that ERA reduces the call blocking probability.…”
Section: Related Workmentioning
confidence: 99%
“…Consequently, the objective function value can be increased by increasing x s to min l∈L(s) {x l s } without violating any constraint. Note that admission control techniques, e.g., the technique in [6], have to be used to decide wether (11) has a feasible solution or not. Now we make the following observation on problem (11).…”
Section: Deterministic Delay Requirements and Pgpsmentioning
confidence: 99%
“…It is also shown that in general, there is much to be gained from using nonuniform reservation policies. Also, [9] studies the problem of resource allocation and CAC in a network with PGPS scheduling. Various nonuniform resource allocation policies were handled and their qualitative performance compared.…”
Section: Related Workmentioning
confidence: 99%